2010
DOI: 10.1007/s00383-010-2588-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic value of the Ki-67 in Wilms’ tumor: experience with 48 cases

Abstract: The results support the conclusion that Ki-67 is a relevant marker for assessing the proliferative activity and tumor cell dynamics of nephroblastoma, but it may not be a good clinical prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The mean proliferation index of blastemal components was 58.9±26.8 in the present study. But this ratio was lower in the other studies [10,37,38]. Both for the Ki67 and TERT staining, the epitope retrieval procedure is the most crucial step.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The mean proliferation index of blastemal components was 58.9±26.8 in the present study. But this ratio was lower in the other studies [10,37,38]. Both for the Ki67 and TERT staining, the epitope retrieval procedure is the most crucial step.…”
Section: Discussionmentioning
confidence: 62%
“…For example, the blastemal component had the highest proliferative activity in three studies, and the authors demonstrated that the blastemal component was a highly significant indicator of metastases and aggressive outcome in WT [29,35,36]. However in two other studies, the highest Ki67 index was determined in the epithelial component [10,36]. In the present study, we determined the highest proliferative activity in the blastemal component, and this rate was adopted as the proliferation index of the tumor.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…With respect to tumor proliferative index, the three histological components of nephroblastomas (blastemal, epithelial and stromal) are known to have different proliferative potentials, with the highest proliferative index reported to occur in the epithelium 24 , 25 , 26 , 27 . The rationale behind this finding has not been fully elucidated so far, since the epithelial component is universally considered to be more differentiated than the other ones 26 , 27 .…”
mentioning
confidence: 99%